Green Branding Strategy and Consumer Loyalty: A Study on Environmentally Friendly Products - Asakdiyah, Salamatun; Aditi, Bunga; Suteja, I Gede Novian (Jurnal Informatika Ekonomi Bisnis, 2025)
This study aims to analyze the influence of green branding strategy on consumer loyalty by considering the mediating role of brand trust among eco-friendly product consumers in Central Java. The research employed an explanatory quantitative approach with a survey design. The population consisted of consumers of green cosmetics, organic food, and eco-labeled household products, with a sample of 140 respondents selected using purposive sampling. Data were collected through an online questionnaire using a 5-point Likert scale adapted from previous studies. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The findings reveal that green branding strategy has a positive and significant impact on consumer loyalty, both directly and indirectly through brand trust. The results indicate that the stronger the green branding strategy implemented by a company, the higher the consumer trust, which in turn fosters greater loyalty. Brand trust serves as a partial mediator, implying that while green branding strategy can directly enhance loyalty, its effect becomes stronger when consumers also trust the brand’s sustainability commitment. Theoretically, this study enriches the green marketing literature by providing empirical evidence of the strategic role of green branding in building loyalty through the psychological mechanism of trust. Practically, it suggests that companies should strengthen environmental information transparency, consistent brand communication, and sustainable innovation to build both trust and long-term loyalty. From a policy perspective, the study highlights the importance for regulators to strengthen green labeling standards and enhance consumer education in order to reduce greenwashing practices.